2017
DOI: 10.1177/0961203317728810
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of flares in systemic lupus erythematosus patients: data from a multiethnic Latin American cohort

Abstract: Purpose The purpose of this paper is to determine the factors predictive of flares in systemic lupus erythematosus (SLE) patients. Methods A case-control study nested within the Grupo Latino Americano De Estudio de Lupus (GLADEL) cohort was conducted. Flare was defined as an increase ≥4 points in the SLEDAI. Cases were defined as patients with at least one flare. Controls were selected by matching cases by length of follow-up. Demographic and clinical manifestations were systematically recorded by a common pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…6,7 In Latin America, studies performed by GLADEL (Grupo Latino Americano De Estudio del Lupus) demonstrated that in patients with SLE, the risk of damage accrual increases with each flare, regardless of flare severity and independently of other known risk factors, such as gender, age at diagnosis, disease duration, high disease activity, previous damage, the presence of antiphospholipid antibodies and antiphospholipid syndrome, high-dose corticosteroids and immunosuppressants, non-Caucasian race/ethnicity, and socio-economic factors. 8,9 Since 2011, belimumab, a new generation biologic therapy, has become available for adults with SLE 10,11 and children 5-17 years of age with childhood-onset SLE. 12 Belimumab is a human, immunoglobulin 1k monoclonal antibody that binds and antagonises the biological activity of circulating B-cell activating factor (BAFF), also known as B-lymphocyte stimulator (BLyS), which is elevated in patients with SLE and promotes abnormal B-cell activation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In Latin America, studies performed by GLADEL (Grupo Latino Americano De Estudio del Lupus) demonstrated that in patients with SLE, the risk of damage accrual increases with each flare, regardless of flare severity and independently of other known risk factors, such as gender, age at diagnosis, disease duration, high disease activity, previous damage, the presence of antiphospholipid antibodies and antiphospholipid syndrome, high-dose corticosteroids and immunosuppressants, non-Caucasian race/ethnicity, and socio-economic factors. 8,9 Since 2011, belimumab, a new generation biologic therapy, has become available for adults with SLE 10,11 and children 5-17 years of age with childhood-onset SLE. 12 Belimumab is a human, immunoglobulin 1k monoclonal antibody that binds and antagonises the biological activity of circulating B-cell activating factor (BAFF), also known as B-lymphocyte stimulator (BLyS), which is elevated in patients with SLE and promotes abnormal B-cell activation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have confirmed that HCQ is protective against flares in SLE. In a large case control study of 465 patients with SLE, older age at diagnosis of SLE and HCQ use were the only protective variables amongst numerous examined variables . Similarly, in a randomized, placebo‐controlled trial of 24 patients, Meinão et al found that HCQ reduced disease exacerbation rates, prednisone dose, and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) scores in SLE .…”
Section: Discussionmentioning
confidence: 98%
“…In systemic lupus erythematosus, for which they were better studied, they have beneficial effects on general and disease-free survival, with a reduction in the risk and delay of quiescent disease reactivation, improvement of the metabolic profile, and protection against occurrence of serious infections. (5,6,16) Their possible mechanisms of action in the pathophysiology of AIH include inhibition of the processing and presentation of antigens, inhibition of cytokine release (interleukins 1, 2, and 6; tumor necrosis factor α; and interferon-γ), inhibition of the T helper 17 response (inhibition of the release of interleukins 6, 17, and 22), decreased natural killer cell activity, inhibition of polymorphonuclear chemotaxis, and inhibition of the activity of cytotoxic T lymphocytes and clusters of differentiation (CD)4+ T lymphocytes with autoreactivity. (17,18) In the current study, possible biases that could have interfered with the results were avoided.…”
Section: Discussionmentioning
confidence: 99%